Association between anti‐fibrillin‐2 protein induced retinal degeneration via intravitreous delivery and activated TGF‐β signalling in mice. (2nd March 2022) - Xu, Furu; Guo, Dadong; Jiang, Qian; Zhang, Ruixue; Yu, Ting; Yin, Xuewei; Wu, Shanshan; Liu, Dezheng; Wen, Ying; Wu, Jianfeng; Bi, Ailing; Jiang, Wenjun; et al.
Abstract: Fibrillin‐2 (FBN2) is a major component of tissue microfibrils, and the decrease of FBN2 perturbs the signalling events mediated by transforming growth factor‐β (TGF‐β), thereby playing a role in macular degeneration. However, the association between the retinal degeneration resulting from the abnormality of FBN2 and the activation of TGF‐β signalling has not been fully addressed. In the present study, the mice were divided into a normal control group (NC group), a phosphate‐buffered saline (PBS) injection group (PBS group), and an anti‐FBN2 protein injection group (anti‐FBN2 group), and the mice in PBS and anti‐FBN2 groups received the relevant treatment via the intravitreal injection once a week for three consecutive weeks. One week later after injection, the retinal morphology and visual function of the fundus were detected. Further, the expression of FBN2, TGF‐β1, TGF‐β2 and TGF‐β3 in retina was measured using quantitative polymerase chain reaction and enzyme‐linked immunosorbent assay (ELISA), respectively. As a result, fundus examination suggests that after intravitreous injection of anti‐FBN2 protein, there were a large patchy yellow white degeneration region and numerous pigmentations in the retina in anti‐FBN2‐treated mice; by contrast, there was no apparent change in mice from the NC and PBS groups. The retina suffered markedly damage, and the thickness of whole retina and outer nuclear layer markedly thinned. The expression of FBN2 was decreased whereas the levels of TGF‐β1, TGF‐β2 and TGF‐β3 were upregulated. Together, our findings indicate that the intravitreous delivery of anti‐FBN2 protein could induce retina degeneration in mice, accompanied by the higher activated TGF‐β. The retinal degeneration mouse model established will provide a platform for the investigation of the retinal diseases.